Seismic Behavior of Short Concrete Columns with Prestressing Steel Wires - Deng Zong-Cai; Jumbe R. Daud; Li Hui (Advances in Materials Science and Engineering)
The seismic behavior of short circular reinforced concrete columns was studied by testing seven columns retrofitted with prestressing steel wire (PSW), subjected to combined constant axial compression and lateral cyclic load. The main test parameters were configuration index of PSW, prestressing level of PSW, and axial compression ratio. An analysis and discussion of the test results including failure mode, hysteresis curves, skeleton curves, ductility, and degradation of stiffness was done. The results show that the seismic performance of the retrofitted specimens could be effectively enhanced even if the axial compression ratio of columns reached 0.81. The ductility index and the energy absorption capacity of the retrofitted specimens increase with the prestressing level of PSW. The formulas for calculating shear capacity of RC short columns strengthened with PSW were proposed which may be useful for future engineering designs and researches.